Skills upgrading for newly qualified surgeon: Is the district hospital in Kenya suitable? - Ojuka D., (The Annals of African Surgery, 2008)
Background: Surgical training in many settings involves acquisition of both knowledge and skill in an environment of adequate caseloads and dedicated supervision. With adequate surgical activity in these settings, the trainee’s confidence is boosted to the point of independence. This skill acquisition is a continuous process, especially so for those who qualify from an exit training program like the one at the University of Nairobi (UON). The continuity is maintained for two years after the masters in surgery program under an experienced surgeon leading to registration by the medical board. This seems to have changed with the posting of newly qualified surgeons to the district hospitals, which has meant a transition from trainee to service provider in the absence of supervision.